16 Days Campaign, Georgia
1. Radio Bridge: Baku, Tbilisi, Jerevan, Organized by WomenAid International - Caucasus / Georgia, Produced by Georgian Radio Network, Financed by Open Society Institute (File name: Caucasus.Radio-Bridge.MP3 – 39 min. 52 sec.) 2. Produced by InterNews (File name: C16D.2002 - public service announcement – Georgia.wmv – 43 sec.)